2013
DOI: 10.1167/13.14.16
|View full text |Cite
|
Sign up to set email alerts
|

Aftereffects support opponent coding of face gender

Abstract: Many aspects of faces derived from structural information appear to be neurally represented using norm-based opponent coding. Recently, however, Zhao, Seriès, Hancock, and Bednar (2011) have argued that another aspect with a strong structural component, namely face gender, is instead multichannel coded. Their conclusion was based on finding that face gender aftereffects initially increased but then decreased for adaptors with increasing levels of gender caricaturing. Critically, this interpretation rests on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 43 publications
(74 reference statements)
2
46
1
Order By: Relevance
“…The tuning of the facial gender aftereffect therefore appeared similar to the tuning of the tilt aftereffect, if a sufficiently broad range of adaptors is considered. Several subsequent studies have also found that facial expression (Skinner & Benton, 2010), gender (Pond et al, 2013), and identity (McKone et al, 2014) aftereffects increase over a broad range of adapting values. These results are inconclusive, since they are consistent with either opponent-channel encoding, or with a scheme involving multiple broadly tuned channels.…”
Section: Evidence From Aftereffects For Norm-based Representation Of mentioning
confidence: 86%
See 4 more Smart Citations
“…The tuning of the facial gender aftereffect therefore appeared similar to the tuning of the tilt aftereffect, if a sufficiently broad range of adaptors is considered. Several subsequent studies have also found that facial expression (Skinner & Benton, 2010), gender (Pond et al, 2013), and identity (McKone et al, 2014) aftereffects increase over a broad range of adapting values. These results are inconclusive, since they are consistent with either opponent-channel encoding, or with a scheme involving multiple broadly tuned channels.…”
Section: Evidence From Aftereffects For Norm-based Representation Of mentioning
confidence: 86%
“…It has been suggested that shifts in neutral category boundaries can differentiate locally repulsive from renormalising aftereffects if one compares the magnitudes of shifts induced by different 'strengths' of adaptor (Burton, Jeffery, Skinner, Benton, & Rhodes, 2013;Jeffery et al, 2010Jeffery et al, , 2011McKone et al, 2014;Pond et al, 2013;Skinner & Benton, 2010, 2012Zhao et al, 2011). A continuum of facial images morphing between different genders (for example) can be thought of as a one-dimensional slice through an artificial face space.…”
Section: Evidence From Aftereffects For Norm-based Representation Of mentioning
confidence: 99%
See 3 more Smart Citations